ENTREPRENEURIAL ECOSYSTEMS, UNIVERSITIES AND UKRAINIAN INNOVATION POLICY - Kolomytseva, Olena; Porev, Sergey (Збірник наукових праць Черкаського державного технологічного університету. Серія: Економічні науки, 2018)
<p class="docData;DOCY;v5;7721;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">The article is devoted to the problem of the formation of entrepreneurial ecosystems as a medium of growth of small firms with the participation of universities, as well as aspects of state policy in the field of innovation and small business development. It is shown that domestic universities, as a rule, adhere to the traditional innovative approach of cooperating with entrepreneurship on the basis of technology transfer and obtaining a direct financial result. The provisions of the Strategy for the development of small and medium enterprises and the role of universities in these aspects of state policy remain conceptually uncertain. It is proved that universities in Ukraine are not focused on the formation of entrepreneurial ecosystems and in support of small businesses. An example of the university unit's activity, whose cooperation with small firms contributes to the formation of a business ecosystem, is considered. The possibilities of increasing the role of the universities of the country in the formation of entrepreneurial ecosystems and more productive cooperation with small business are substantiated. The project of the Strategy of innovation development of the country for the period till 2030 is considered and it is proposed to pay more attention to creation of enterprise ecosystems with the participation of universities, and also to introduce the approach of knowledge exchange between universities and business on the basis of positive experience of a number of leading countries. Keywords: entrepreneurial ecosystem, university, high growth firm, small business, innovation, technology transfer, knowledge exchange.